Analisis Stilistika Lirik Lagu “Asmalibrasi” Karya Soegi Bornean - Ayo Suwaryo (Concept: Journal of Social Humanities and Education, 2022)
This article contains a stylistic analysis of the lyrics of the song “Asmalibrasi” by Soegi Bornean. The discussion of this article focuses on the aspects of connotative diction and the use of figure of speech in the lyrics. The research method used to analyze the lyrics of the song is a qualitative descriptive method. The data analysis techniques used in this study are (1) selecting data; (2) code; (3) classifying data; (4) data description; and (5) data interpretation. The object of this research is the lyrics of the song "Asmalibrasi" by Soegi Bornean. From the analysis carried out, it shows that the diction contained in the lyrics of the song is mostly connotative. The connotative diction that is widely used in the lyrics of the song is a manifestation of the songwriter's creativity when creating the lyrics to his songs. In addition, the lyrics of the song also use a lot of figure of speech including, metaphorical figure of speech, allegorical figure of speech and hyperbole figure of speech.